2014
DOI: 10.1021/jo500966m
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Additives on the Zinc Carbenoid-Mediated Cyclopropanation of a Dihydropyrrole

Abstract: The synthesis of a key intermediate in the preparation of oral antidiabetic drug Saxagliptin is discussed with an emphasis on the challenges posed by the cyclopropanation of a dihydropyrrole. Kinetic studies on the cyclopropanation show an induction period that is consistent with a change in the structure of the carbenoid reagent during the course of the reaction. This mechanistic transition is associated with an underlying Schlenk equilibrium that favors the formation of monoalkylzinc carbenoid IZnCH2I relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Regarding SAXA degradation process, reactions (Equations (10)–(12)) were constructed, based on specific available literature [16,30,31], amidine, epimer, and formyl amide formation mechanisms [19,32,33,34,35,36,37] and own experimental measurements. Jones et al identified solvent’s propensity to participate in proton transfer and ESCA autocatalysis as the two main contributors of SAXA to ESCA conversion [16]; however, to our set of solid-state reactions, this does not directly apply, owing to slower reaction rates and specific micro-environmental conditions, established by tablet excipients.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding SAXA degradation process, reactions (Equations (10)–(12)) were constructed, based on specific available literature [16,30,31], amidine, epimer, and formyl amide formation mechanisms [19,32,33,34,35,36,37] and own experimental measurements. Jones et al identified solvent’s propensity to participate in proton transfer and ESCA autocatalysis as the two main contributors of SAXA to ESCA conversion [16]; however, to our set of solid-state reactions, this does not directly apply, owing to slower reaction rates and specific micro-environmental conditions, established by tablet excipients.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, all attempts to obtain suitable crystals for X-ray analysis by recrystallization led to the isolation of the diiodozinc complex 1 ′ (bipy-ZnI 2 ) with the corresponding nitrogen ligands (Figure S1 and Table S1). This can be understood by considering the change in chemical structure through a Schlenk equilibrium, which is often proposed for main-group metal-based organometallic reagents having metal–halogen bonds, such as Grignard and organozinc reagents (Scheme a). , The Schlenk equilibrium is known to proceed via self-transmetalation of gem -dizinciomethanes R 2 C­(ZnX) 2 to produce dimeric, trimeric, and oligomeric organozinc species (Scheme b). The methylene proton signal of the bipyridine complex 1 in CD 2 Cl 2 disappeared gradually at room temperature, and the formation of an insoluble white solid was observed.…”
mentioning
confidence: 99%
“…Since ligand exchange shown in Scheme b probably proceeds through a bimolecular associative process, we postulated that the bulky ligand 6-mesityl-2,2′-bipyridine (MesBipy) would prevent the Schlenk equilibrium and generate the more stable gem -di­(iodozincio)­methane species . When a mixture of gem -di­(iodozincio)­methane and 6-mesityl-2,2′-bipyridine (1:2 ratio) was stirred in THF at 25 °C, formation of a yellow precipitate was observed.…”
mentioning
confidence: 99%
“…Due to their synthetic 6 and pharmaceutical importance, substantial ongoing efforts have been devoted to develop efficient methodologies for building such an important family of cyclopropane-fused pyrrolidine scaffolds. Traditionally, these structures could be prepared via the Simmons–Smith reaction of N-protected dihydropyrroles 7 or the direct cyclopropanation of pyrrole derivatives employing electrophilic metallocarbenoids ( Scheme 1a ). 8 Other methods from non-pyrrole starting materials have also been reported.…”
Section: Introductionmentioning
confidence: 99%